Pengaruh Kepemimpinan Kepala Sekolah Terhadap Disiplin Kerja Guru Di Sekolah Menengah Kejuruan (SMK) Kansai Pekanbaru - Febrina, Dian (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
This research was conducted at Smk Kansai Pekanbaru Vocational High School, the purpose of this research was to find out the influence of the headmaster's leadership on the discipline of teacher work, with the population in this study being 34 people. Data collection conducted through the dissemination of questionnaires and data analysis techniques used at a significant rate of 0.05 is a validity test, a reality test with alpha cronbach, a t test, as well as simple linear regression analysis and R Square determination analysis ( ). The results of analysis and data of this study using the help of SPSS version 23, obtained the results of simple linear regression equations are Y = 17,187 + 1,189 X. Based on the results of the study on t> test showed the value of thitung>ttabel (4,556 > 2,037) then the results of this study showed that the leadership of the principal significantly influenced the discipline of teacher work. Based on data obtained from the results of correlation analysis between variable X and variable Y obtained R Square ( ) of 0.393 or 39.3%, this indicates that the percentage of contribution of free variable (100%-39,3%)Â 60,7% Â influence to bound variables is 39.3% while the rest is influenced by other variables not studied in this study